2000
DOI: 10.1046/j.1365-2133.2000.03356.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the activity of the disease in patients with cutaneous lupus erythematosus

Abstract: The Systemic Lupus Activity Measure (SLAM) is a system proposed by rheumatologists to measure disease activity in their patients with systemic lupus erythematosus (LE). It involves scoring a group of clinical symptoms and laboratory findings, the maximum possible score being 84. In systemic LE, the mid-point is between 9 and 12. We applied SLAM to 176 patients with cutaneous LE. Ninety-seven had localized discoid LE (L-DLE), 59 had disseminated discoid LE (D-DLE) and 20 had subacute cutaneous LE (SCLE). Eighty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 5 publications
0
65
0
4
Order By: Relevance
“…Entre as manifestações clínicas, fotossensibilidade, alopecia, úlcera oral e fenômeno de Raynaud parecem sugerir pior prognóstico no lúpus cutâneo (16) . Outros estudos clínicos (6,17) sugerem que a sistematização do lúpus eritematoso cutâneo esteja associada com a extensão das lesões cutâneas, com a presença de fenômeno de Raynaud, úlceras orais, fotossensibilidade e positividade de anti-DNA.…”
Section: Discussionunclassified
“…Entre as manifestações clínicas, fotossensibilidade, alopecia, úlcera oral e fenômeno de Raynaud parecem sugerir pior prognóstico no lúpus cutâneo (16) . Outros estudos clínicos (6,17) sugerem que a sistematização do lúpus eritematoso cutâneo esteja associada com a extensão das lesões cutâneas, com a presença de fenômeno de Raynaud, úlceras orais, fotossensibilidade e positividade de anti-DNA.…”
Section: Discussionunclassified
“…Konstitütisyonel semptomlar, deri bulguları, göz, retiküloendotelyal sistem, pulmoner, kardiyovasküler, gastrointestinal, nörolojik sistem ve eklem tutulumu hafif, orta, şiddetli olarak skorlanıp toplamı alınır 74 .…”
Section: Sistemik Lupus Aktivite Değeriunclassified
“…In a recent retrospective study, Parodi et al noted that 60 measures of systemic lupus erythematosus were available, but only three of these appeared useful for dermatologists (Parodi, et al, 2000). Based on their experience with 176 patients with cutaneous LE, Parodi et al found even these scores inadequate for dermatologists and called for revision (Parodi, et al, 2000).…”
Section: Disease Activity Measurements For Skin Diseasementioning
confidence: 99%
“…Based on their experience with 176 patients with cutaneous LE, Parodi et al found even these scores inadequate for dermatologists and called for revision (Parodi, et al, 2000).…”
Section: Disease Activity Measurements For Skin Diseasementioning
confidence: 99%
See 1 more Smart Citation